Post Traumatic Stress Dissorder (PTSD) dan Mekanisme Pertahanan Diri pada Tokoh Utama dalam Novel Shokuzai Karya Minato Kanae - Prayojana, Anaya Hira; Wiriani, Ni Made; Dewi, Ni Made Andry Anita (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2025)
This research, entitled “PTSD And Self Defense Mechanism In The Main Character Of Minato Kanae’s Novel ‘Shokuzai’” This novel tells the death tragedy of their friends, Emily, fifteen years ago. Emily's death and the threats by Emily's mother triggered trauma for the main characters. Their childhood wounds before the incident also exacerbated their PTSD symptoms. Purpose of this research is to identify the symptoms of PTSD in the five main characters Akiko, Sae, Maki, Yuka, and Asako, and to explore the self defense mechanisms they use to cope with their trauma. The method used is descriptive analysis with a literary psychology approach. The theories underlying this research are Freud's self defense mechanism theory and the DSM-5 (APA, 2013). The first analysis showed that the five characters experienced 5 common symptoms of PTSD in DSM-5; traumatic events, intrusive symptoms, avoidance, negative cognitions and mood changes, and hyperarousal. The second analysis revealed that each character applied self defense mechanisms to avoid and cope with trauma. Akiko used three mechanisms, meanwhile the other four characters use four mechanisms. This research reveals that the complexity of psychological issues has varied and significant impacts on an individual’s condition.